Reliability and validity of a novel agility measurement device for badminton players - Utku Kamuk, Y. (African Educational Research Journal, 2020)
The validity and reliability of a novel badminton agility test was examined by making comparisons with reviously established agility tests, namely the T-test and Illinois test. The participants were active high-level badminton players (n = 36) and active non-badminton players (n = 33). The participants performed three tests to assess agility: (a) T-test, (b) Illinois test, and (c) the novel badminton agility test (BAT). Independent samples ttest was used to compare mean scores and paired-samples ttest for the differences between pre-and post-tests. Intraclass correlation coefficient (ICC), paired samples ttest and Bland-Altman plot were used to test the reliability of the agility measurements. The level of agreement between the tests was analyzed by using Cohen`s Kappa (?) and Pearson`s r. Concurrent validity was tested by dispersion plot and coefficient of determination. Construct validity was assessed by independent samples ttest. According to the results, it was found that BAT had a good level of agreement with T-test and Illinois test. BAT was found to be a discriminative test for the badminton and non-badminton players. BAT was strongly correlated to T-test but the correlation to IAT was stronger. Construct and concurrent validity of BAT were found to be high and reliability assessments revealed satisfactory results. It was found that agility assessment by using BAT could be appropriately done for the badminton players. BAT seems to be a valid and reliable agility measurement test for the badminton players, but not for the non-badminton players, and it has concurrent validity, construct validity, and reliability.